2017
DOI: 10.1177/1524838017708782
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurring Substance Use, PTSD, and IPV Victimization: Implications for Female Offender Services

Abstract: The co-occurrence of substance use disorders (SUDs) and post-traumatic stress disorder (PTSD) among women who have been the victims of intimate partner violence (IPV) is complex and causal associations cannot be assumed. Although the presence of co-occurring disorders among IPV victims is a well-established research finding, there is a need for improved understanding of their prevalence and related mental health treatment requirements among female offenders. We review research indicating that service providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 102 publications
(141 reference statements)
2
24
0
Order By: Relevance
“…RC was not significantly associated with abusing alcohol or drugs. Studies on IPV have found consistent associations between IPV and substance use, [46][47][48] so it may be that the independent association of RC with substance abuse was not able to be detected in this sample of abuse survivors. While this study focused on depression as a primary mental health outcome, PTSD is also known to be linked to IPV, 49 and would be useful to study in future research.…”
Section: Discussionmentioning
confidence: 69%
“…RC was not significantly associated with abusing alcohol or drugs. Studies on IPV have found consistent associations between IPV and substance use, [46][47][48] so it may be that the independent association of RC with substance abuse was not able to be detected in this sample of abuse survivors. While this study focused on depression as a primary mental health outcome, PTSD is also known to be linked to IPV, 49 and would be useful to study in future research.…”
Section: Discussionmentioning
confidence: 69%
“…Holistic addiction treatment addresses substance abuse within the context of mental health and trauma. This approach is crucial for women as a large proportion experience co-occurring disorders (60-75%; McKee & Hilton, 2017;Scott et al, 2015).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Bonta and Andrews (2016) explained that treatment services should place less emphasis on addressing noncriminogenic needs due to their lower association with recidivism, unless attending to an offender's noncriminogenic need influences a criminogenic one. For example, offenders with major mental disorders may be unable to reduce their substance use unless both problems are treated (e.g., McKee & Hilton, 2017).…”
Section: The Criminogenic and Noncriminogenic Needs Of General Offendersmentioning
confidence: 99%